(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Emotional experiences fundamentally shape human behavior through intricate neural mechanisms that involve dynamic synaptic modifications across distributed brain networks. This investigation explores the molecular and cellular foundations of emotional processing, examining how synaptic plasticity mechanisms within key limbic structures facilitate the encoding, consolidation, and retrieval of affective memories. Through comprehensive analysis of contemporary neuroscientific research, we demonstrate that emotional processing relies on coordinated activity across amygdaloid, hippocampal, and cortical circuits, where activity-dependent synaptic modifications enable persistent changes in network connectivity. Critical molecular pathways include calcium-dependent kinase cascades, transcriptional regulation through immediate early genes, and neurotrophic factor signaling that collectively support long-term synaptic modifications. Neuromodulatory influences from monoaminergic systems provide contextual regulation of plasticity induction, while homeostatic mechanisms ensure network stability during experience-dependent adaptations. Dysregulation of these processes contributes to psychiatric conditions including depression, anxiety disorders, and trauma-related pathology, suggesting therapeutic targets for intervention. Our findings reveal that emotional processing emerges from complex interactions between excitatory and inhibitory circuits, modulated by neuroendocrine factors and subject to epigenetic regulation that enables lifelong capacity for emotional learning and adaptation.